1991
DOI: 10.1007/bf00035338
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiological attributes of the dry matter economy of bread wheat (Triticum aestivum) through genetic improvement of grain yield potential at different regions of the world

Abstract: The understanding of the changes produced by plant breeding on wheat grain yield and on its determinants, through the study of the behaviour of cultivars released at different times during the breeding process, could be a useful tool to define future selection criteria. The aim of this paper was to examine the genetic improvement effects on bread wheat grain yield potential and on its major physiological determinants in different countries.Generally, it seems that the genetic improvement produced important inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
5
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 69 publications
8
85
5
3
Order By: Relevance
“…Compared to results obtained elsewere, the rate of progress in the yield of spring bread wheat in Southern Brazil is higher than those obtained in Argentina, Australia, Canada, England and the United State of America (Slafer & Andrade, 1991), and lower than those obtained in Mexico in the same period of time. However, these estimates in genetic progress in countries like Australia, England and USA are representative of periods of about a century or more.…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…Compared to results obtained elsewere, the rate of progress in the yield of spring bread wheat in Southern Brazil is higher than those obtained in Argentina, Australia, Canada, England and the United State of America (Slafer & Andrade, 1991), and lower than those obtained in Mexico in the same period of time. However, these estimates in genetic progress in countries like Australia, England and USA are representative of periods of about a century or more.…”
Section: Resultscontrasting
confidence: 74%
“…Such gain was higher than the one obtained by Nedel (1994) in similar trials. Slafer & Andrade (1991) summarized studies of genetic progress in the yield of bread wheat in many countries, and reported annual rates of progress from 5.8 kg ha -1 (India) to 58.4 kg ha -1 (Mexico). Countries like Argentina, Canada, Australia, England, and USA produced intermediate values of genetic gain, suggesting a similar efficiency among their genetic breeding programs (Slafer & Andrade, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, source or sink limitations may operate during different developmental stages, as found in various crops. For wheat, research shows that the crop is mainly sink-limited (Jenner 1979;Savin and Slafer 1991;Slafer and Andrade 1991;Slafer and Savin 1994;Miralles and Slafer 1995;Kruk et al 1997;Borrás et al 2004), as little or no grain weight response has been observed when increases in resource availability per grain (i.e. detached treatments) or reductions in assimilate supply (i.e.…”
Section: Introductionmentioning
confidence: 99%